2019
DOI: 10.3390/e21100991
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Stream Gauge Network Design Using Entropy Theory and Importance of Stream Gauge Stations

Abstract: Stream gauge stations are facilities for measuring stream water levels and flow rates, and their main purpose is to produce the data required to analyze hydrological phenomena. However, there are no specific criteria for selecting the locations and installation densities of stream gauge stations, which results in numerous problems, including regional imbalances and overlapping. To address these issues, a stream gauge network was constructed in this study considering both the transinformation of entropy (object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Gauge placement decisions are made to satisfy a variety of local factors, but the use of gauge data to draw conclusions about watershed hydrology, ecology and human water needs comes with the necessity that the gauge network is representative of the attributes of all rivers 11 . Better accounting for socioecological and environmental heterogeneity in gauge networks will improve hydrologic models 47 Tropical and subtropical upland rivers and their utility in informing water security challenges and strategies for addressing the freshwater biodiversity crisis 12 . Further, given the paucity of water information in some of the world's river basins, additional gauges and advances in alternative data sources can substantially improve the information base upon which water resource-management decisions are made.…”
Section: Discussionmentioning
confidence: 99%
“…Gauge placement decisions are made to satisfy a variety of local factors, but the use of gauge data to draw conclusions about watershed hydrology, ecology and human water needs comes with the necessity that the gauge network is representative of the attributes of all rivers 11 . Better accounting for socioecological and environmental heterogeneity in gauge networks will improve hydrologic models 47 Tropical and subtropical upland rivers and their utility in informing water security challenges and strategies for addressing the freshwater biodiversity crisis 12 . Further, given the paucity of water information in some of the world's river basins, additional gauges and advances in alternative data sources can substantially improve the information base upon which water resource-management decisions are made.…”
Section: Discussionmentioning
confidence: 99%
“…Then, they classified the recent applications of entropy into four groups (including precipitation, streamflow and water level, water quality, and soil moisture and groundwater networks) and investigated them. Joo et al (2019) investigated and redesigned a hydrometric station by implementing two objective functions (i.e., changes in entropy information and the importance of each station according to their priority) using the Euclidean distance. They showed that 8 stations can be implemented instead of 12 ones so that the combination of the selected stations could reflect both the changes of entropy information and the importance of each station.…”
Section: Introductionmentioning
confidence: 99%
“…The study [ 10 ] designed a hydrometric network of watersheds using the concept of marginal entropy, joint entropy and transinformation. The studies [ 11 , 12 , 13 , 14 ] evaluated rainfall monitoring networks and presented the optimal network in terms of network composition. The design of an optimal rainfall monitoring network considering altitude as well as entropy was also investigated [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%